Global Fast Fashion Industry: Present Opportunities and Future Challenges for Sustainability - Faisal, Omar; Mohajan, Haradhan Kumar (Art and Society, 2026)
Fast fashion is a business model that has profoundly changed the fashion industry by creating an efficient supply chain for the rapid production of fashionable merchandise. It has revolutionized in clothing industry with the fulfillment of consumer demand through the development of new styles. On the other hand, it produces a large quantity of harmful raw materials, as well as roughly emits 8-10% of global carbon dioxide (CO2), and disposes excess untreated water and microplastics. The garment workers in this sector are victims of various oppressions, such as low-wages, unhealthy working conditions, and endemic labor injustices. For sustainability, it requires not only technological innovations but also some systemic changes in policies, business practices and consumer behavior to make sure the production is both socially fair and environmentally responsible. This study explores environmental and social implications of fast fashion based on circular economy and environmental justice.